Afghanistan's Development Gains : Progress and Challenges - Haque, Tobias (World Bank, Washington, DC, 2020)
This note outlines some of the major gains that have been achieved in Afghanistan since the US-led intervention in 2001. The analysis is informed by comparisons to development progress and outcomes in other low-income countries over the same period. Afghanistan remains mired in conflict and faces immense development challenges. However, donor and government programs executed in the context of rapid economic growth and sound macroeconomic management have supported rapid improvements in provision of basic public services and infrastructure over the past two decades. While progress has been uneven and data to assess progress is sometimes limited or unreliable, increased access to services and infrastructure has driven huge development gains, often far outpacing progress achieved in other low-income countries. Against many indicators, Afghanistan is now performing similarly to other countries at its level of incomes, while receiving similar levels of civilian aid. Development gains remain fragile, however, and continued international support will be required to avoid reversal of recent progress. Section two outlines the extent of international assistance to Afghanistan since 2001. Section three reviews economic performance and overall macroeconomic management. Section four shows how access to services and infrastructure has improved. Section five shows how improved access to services has led to major improvements in development outcomes, including for women. The final section highlights continued weakness in governance and the need for ongoing international support.